Long Term Impact on Lung Function of Patients With Moderate and Severe COVID-19. A Prospective Cohort Study - Qureshi, Sonia; Nasir, Nosheen; Rashid, Naveed; Ahmed, Naveed; Haq, Zoya; Qamar, Farah (Frontiers in Public Health, 2021)
Background In Pakistan, the cases of COVID-19 have declined from 6000 per day in June to 600 in September 2020. A significant number of patients continue to recover from the disease, however, little is known about the lung function capacity among survivors. We aim to determine the long-term impact on lung function capacity in patients who have survived moderate or severe COVID-19 disease in a resource-poor setting. Methods This prospective cohort study will be conducted at Aga Khan University Hospital (AKUH), Karachi Pakistan. Patients 15 years and above who have survived an episode of moderate or severe COVID-19, have reverse transcriptase-polymerase chain reaction (RT-PCR) positive for COVID 19 (nasopharyngeal or oropharyngeal) will be included. Patients with a pre-existing diagnosis of obstructive or interstitial lung disease, lung fibrosis, lung cancers, connective tissue disorders, autoimmune conditions affecting the lungs, underlying heart disease, history of syncope and those who refuse to participate will be excluded from the study. Pulmonary function will be assessed using spirometry and diffusion lung capacity for carbon monoxide (DLCO) at three- and six-months interval from the time of discharge from the hospital. Additionally, a chest X-ray and CT-chest will be performed if clinically indicated after consultation with the study pulmonologist or Infectious Disease (ID) physician. Echocardiogram (ECHO) will be performed to look for pulmonary hypertension at the three month visit and repeated at six months in case any abnormality is identified in the initial ECHO. Data analysis will be performed using standard statistical software. The study was approved by the Ethical Review Committee (ERC) of the institution (ERC reference number 2020-4735-11311). Strengths and Limitations of the Study This cohort study will provide evidence on the long-term impact on lung function among COVID-19 survivors with moderate to severe disease. Such data will be key in understanding the impact of the disease on vital functions and will help devise rehabilitative strategies to best overcome the effects of disease. However, this will be a single-center, study recruiting only a limited number of COVID-19 survivors.